Double-sided printing film and preparation method thereof

By adopting a double-sided printing film with a three-layer composite structure, using materials such as polyethylene terephthalate, polypropylene and modified titanium dioxide, combined with coextrusion treatment technology, the problem of insufficient performance of the double-sided printing film in the existing technology is solved, and the effects of low light transmission, high mechanical properties and good weather resistance are achieved.

CN119898104AActive Publication Date: 2025-04-29NINGBO QINBANG NEW MATERIAL TECH CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202510389819.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

It is difficult to produce a double-sided printing film with good light transmittance, mechanical properties and weather resistance in the prior art, and the preparation method needs to be optimized.

Method used

A double-sided printed film with a three-layer composite structure is adopted, wherein the surface layer is prepared from polyethylene terephthalate, polypropylene, modified titanium dioxide and additives, and the core layer is prepared from polyethylene terephthalate, polypropylene and modified titanium dioxide, and obtained by coextrusion treatment.

Benefits of technology

The light transmittance of the printing film is reduced, the printing effect and aesthetics of the printing products are improved, the tensile and puncture resistance of the printing film is enhanced, and the weather resistance and market competitiveness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a double-sided printing film and a preparation method thereof, the double-sided printing film is composed of three layers of compounds, the middle layer is a core layer, and the two sides of the core layer are surface layers; wherein the surface layer is prepared from polyethylene glycol terephthalate, polypropylene, modified titanium dioxide and auxiliaries; the core layer is prepared from polyethylene glycol terephthalate, polypropylene and modified titanium dioxide. The preparation method comprises the following steps: mixing modified titanium dioxide, an auxiliary agent, polyethylene glycol terephthalate and polypropylene, and carrying out injection molding to obtain the surface layer; the modified titanium dioxide, polyethylene glycol terephthalate and polypropylene are mixed and then subjected to injection molding, and a core layer is obtained; and co-extruding the surface layer and the core layer to obtain the double-sided printing film. The double-sided printing film provided by the invention has ultra-low light transmittance, weather resistance, tensile property and puncture resistance, the printing effect and aesthetic property are improved, and the market competitiveness is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polyester base film manufacturing, and in particular to a double-sided printing film and a preparation method thereof. Background Art

[0002] Double-sided printed film is a material with broad application prospects, and its uses are wide and diverse. Such products are mainly used in packaging, printing, advertising, electronic equipment and other fields. For example, double-sided printed film is widely used in the packaging field as automatic packaging materials, food packaging materials, mask packaging materials, etc., further enhancing the safety and aesthetics of the product. In addition, double-sided printed film is also used in the screen protection of smart devices, plastic sealing of gift boxes, and the production of various labels and advertising light boxes.

[0003] Among them, double-sided printed low-light transmittance film is a high-performance film material with broad application prospects. Since this type of material has good printability, it is suitable for the production of hanging printed posters, and the low light transmittance of the printed film ensures that the patterns printed on both sides will not affect each other, with good visual effects.

[0004] However, at present, the production of double-sided printed film products with good light transmittance, good mechanical properties and weather resistance and the preparation method are in urgent need of optimization and improvement. Summary of the invention

[0005] One object of the present application is to provide a double-sided printing film and a preparation method thereof, which are helpful to reduce the light transmittance of the double-sided printing film and improve the printing effect and aesthetics of the printed product.

[0006] Another object of the present application is to provide a double-sided printed film and a preparation method thereof, which are beneficial to improving the tensile properties and weather resistance of the double-sided printed film and enhancing the performance of printed products.

[0007] Another object of the present application is to provide a double-sided printed film and a preparation method thereof, which are conducive to improving the adhesion between the layers of the double-sided printed film, further enhancing the puncture resistance, and improving the market competitiveness of printed products.

[0008] In order to achieve the above objectives, the technical solution adopted in the present application is: a double-sided printing film, which is composed of three layers of composite materials, wherein the middle layer is a core layer, and both sides of the core layer are surface layers; The surface layer is prepared from polyethylene terephthalate, polypropylene, modified titanium dioxide and additives; The core layer is prepared from polyethylene terephthalate, polypropylene and modified titanium dioxide.

[0009] In some embodiments, the modified titanium dioxide is titanium dioxide with polypropylene grafted with maleic anhydride on the surface.

[0010] In some embodiments, the preparation steps of the modified titanium dioxide are: S100, putting titanium dioxide powder into anhydrous ethanol and performing ultrasonic treatment for 10 min to 30 min to obtain a first solution; S200, placing the first solution into a mixed solution of a silane coupling agent and anhydrous ethanol, stirring and reacting for 1 h to 3 h to obtain a first mixture; S300, centrifugally treating the first mixture, washing and drying the solid matter obtained by the centrifugation to obtain a first powder; S400, providing a mixed solution of xylene and ethanol, and placing the first powder and polypropylene grafted maleic anhydride into the mixed solution to obtain a second mixture; S500, adding dibenzoyl peroxide to the second mixture, heating to a first temperature to perform a grafting reaction, and obtaining a third mixture; S600, centrifugally treating the third mixture, washing and drying the solid matter obtained by the centrifugation to obtain modified titanium dioxide.

[0011] In some embodiments, the ratio of the molar number n1 of maleic anhydride groups in the polypropylene grafted maleic anhydride to the molar number n2 of epoxy groups in the first powder is: 1 / 10≤n1:n2≤1 / 2.

[0012] In some embodiments, the mass fraction of the polyethylene terephthalate in the surface layer is 50wt.%~60wt.%, the mass fraction of the polypropylene is 10wt.%~20wt.%, the mass fraction of the modified titanium dioxide is 5wt.%~15wt.%, and the mass fraction of the auxiliary agent is 5wt.%~10wt.%.

[0013] In some embodiments, the mass fraction of the polyethylene terephthalate in the core layer is 50wt.%~60wt.%, the mass fraction of the polypropylene is 20wt.%~30wt.%, and the mass fraction of the modified titanium dioxide is 10wt.%~20wt.%.

[0014] In some embodiments, the mass fraction of modified titanium dioxide in the core layer is greater than the mass fraction of modified titanium dioxide in the surface layer.

[0015] In some embodiments, the particle size of the modified titanium dioxide is 30 nm to 60 nm.

[0016] In some embodiments, the auxiliary agent includes fluorescent whitening agent, stearic acid amide, oleic acid amide, nano calcium carbonate and zinc oxide.

[0017] In some embodiments, among the auxiliary agents, the mass fraction of the fluorescent whitening agent is 10wt.%~20wt.%, the mass fraction of the stearic acid amide is 10wt.%~20wt.%, the mass fraction of the oleic acid amide is 5wt.%~15wt.%, the mass fraction of the nano-calcium carbonate is 30wt.%~45wt.%, and the mass fraction of the zinc oxide is 15wt.%~25wt.%.

[0018] In some embodiments, the thickness of the surface layer is 40 μm to 80 μm, and the thickness of the core layer is 200 μm to 400 μm.

[0019] According to another aspect of the present application, a method for preparing a double-sided printed film is also provided, comprising the steps of: A100, mixing the modified titanium dioxide and the additive by a high-speed mixer to obtain a first filler; A200, mixing the first filler, polyethylene terephthalate and polypropylene by a high-speed mixer and then performing injection molding to obtain a surface layer; A300, the modified titanium dioxide, polyethylene terephthalate and polypropylene are mixed by a high-speed mixer and then injection molded to obtain a core layer; A400, the surface layer and the core layer are co-extruded to obtain the double-sided printed film.

[0020] Compared with the prior art, the beneficial effects of this application are: (1) The present invention provides a double-sided printing film and a preparation method thereof, which further reduces the overall light transmittance of the printing film by constructing a double-sided printing film with three composite layers, including a surface layer with low light transmittance and a core layer with ultra-low light transmittance, thereby improving the printing effect and aesthetics of the printed product.

[0021] (2) The present invention provides a double-sided printed film and a preparation method thereof, which enhances the bonding performance between the three composite layers by modifying titanium dioxide, so that the modified titanium dioxide is stably distributed between the layers, while enhancing the interfacial interaction between the layers, enhancing the tensile strength and puncture resistance of the printed film, thereby reducing damage during use.

[0022] (3) The present invention provides a double-sided printed film and a preparation method thereof, which increases the weather resistance of the printed film by adding polypropylene to the printed film matrix, and exhibits better stability under ultraviolet irradiation and high temperature environment, thereby extending the service life. DETAILED DESCRIPTION

[0023] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0024] In the description of the present application, it should be noted that directional words, such as the terms "center", "lateral", "longitudinal", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", etc., indicating directions and positional relationships are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and cannot be understood as limiting the specific scope of protection of the present application.

[0025] It should be noted that the terms "first", "second", etc. in the description and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.

[0026] The terms "including" and "having" and any variations thereof in the specification and claims of this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0027] According to one aspect of the present invention, a double-sided printing film is formed by a three-layer composite, wherein the middle layer is a core layer, and both sides of the core layer are surface layers; The surface layer is prepared from polyethylene terephthalate, polypropylene, modified titanium dioxide and additives; The core layer is made of polyethylene terephthalate, polypropylene and modified titanium dioxide.

[0028] By constructing a three-layer composite structure in a double-sided printed film, it is convenient to regulate the performance of the printed film, wherein the core layer has an ultra-low transmittance, and the surface layers with low transmittance are distributed on both sides, further reducing the overall transmittance of the printed film and improving the printing effect and aesthetics of the printed product. Modified titanium dioxide grafted with polypropylene grafted maleic anhydride (PP-g-MAH) is added to the blending system of polyethylene terephthalate (PET) and polypropylene (PP). The grafted PP-g-MAH acts as a good compatibilizer. While improving the compatibility of PET and PP, it enhances the interfacial force, making the bonding performance between each phase region and each layer stronger, which is beneficial to improving the tensile and puncture resistance of the double-sided printed film. Furthermore, the addition of modified titanium dioxide grafted with PP-g-MAH is beneficial to improving the defects in the blending system, further enhancing the oxygen barrier and water vapor barrier properties of the printed film, and is beneficial to improving the weather resistance when used outdoors.

[0029] It is understandable that when PET is used as a printing film substrate, PET has the advantages of high transparency, high gloss, chemical stability, thermal stability and environmental sustainability, which makes it widely used in the printing products industry. However, the high processing difficulty and high cost of PET limit its application. Furthermore, PP has good toughness and impact resistance. Blending with PET can significantly improve the impact strength and tensile strength of the printed film, and improve the processing performance and reduce the processing difficulty. Especially when used outdoors, PP has good water resistance, gas barrier properties and heat resistance, which reduces the sensitivity of the PET component in the system to moisture and improves the stability of the PET component in a humid or hot environment, thereby enhancing the performance of the double-sided printed film. Furthermore, the use of PP is conducive to reducing the production cost of the printed film and has good economic benefits.

[0030] In some embodiments, the modified titanium dioxide is titanium dioxide with polypropylene grafted with maleic anhydride on the surface.

[0031] It is understandable that titanium dioxide powder is a white filler with excellent performance, with high hiding power, high whiteness and high refractive index, which makes it have strong scattering ability in the visible light range, which helps to improve the whiteness of the printed film and reduce the transmittance of light. Further, by grafting PP-g-MAH on titanium dioxide powder, the interfacial compatibility between it and the PET and PP components in the printed film matrix is ​​increased, while optimizing the processing performance of the blending system, the stress concentration phenomenon at the interface is reduced, thereby improving the elongation at break and the breaking strength of the printed film. In other words, the titanium dioxide powder after grafting PP-g-MAH is conducive to enhancing the bonding force between itself and the matrix, reducing the phenomenon of shedding, and the modified titanium dioxide is distributed in both the surface layer and the core layer. Due to the effect of the modified titanium dioxide, the mutual bonding performance between the layers becomes better, further improving the tensile strength and puncture resistance of the printed film, so that it has good performance in various use environments.

[0032] In some embodiments, the preparation steps of modified titanium dioxide are: S100, putting titanium dioxide powder into anhydrous ethanol and performing ultrasonic treatment for 10 min to 30 min to obtain a first solution; S200, placing the first solution into a mixed solution of a silane coupling agent and anhydrous ethanol, stirring and reacting for 1 h to 3 h, to obtain a first mixture; S300, centrifugally treating the first mixture, washing and drying the solid matter obtained by the centrifugation to obtain a first powder; S400, providing a mixed solution of xylene and ethanol, placing the first powder and polypropylene grafted maleic anhydride into the mixed solution to obtain a second mixture; S500, adding dibenzoyl peroxide to the second mixture, heating to the first temperature to perform a grafting reaction, and obtaining a third mixture; S600, the third mixture is centrifuged, and the solid matter obtained by the centrifugation is washed and dried to obtain modified titanium dioxide.

[0033] The preparation steps of the modified titanium dioxide provided in the present application have the advantages of a simple preparation method, fewer operation steps, and higher production efficiency, which is conducive to large-scale production process.

[0034] In some embodiments, the ratio of the molar number n1 of maleic anhydride groups in polypropylene grafted maleic anhydride to the molar number n2 of epoxy groups in the first powder is: 1 / 10≤n1:n2≤1 / 2, specifically, the ratio of n1:n2 can be 1 / 10, 1 / 9, 1 / 8, 1 / 7, 1 / 6, 1 / 5, 1 / 4, 1 / 3, 1 / 2, and further preferably, the ratio of the molar number n1 of maleic anhydride groups in polypropylene grafted maleic anhydride to the molar number n2 of epoxy groups in the first powder is: 1 / 6≤n1:n2≤1 / 2. It can be understood that the first powder obtained by the silane coupling agent treatment has more epoxy groups, and a part of the epoxy groups react with the maleic anhydride groups in PP-g-MAH, so that PP-g-MAH is grafted onto the first powder to obtain modified titanium dioxide. The remaining epoxy groups react with the terminal carboxyl groups in PET, increasing the compatibility while increasing the bonding force between the PET, PP and modified titanium dioxide layers, so that the printed film maintains good mechanical stability during use.

[0035] In some embodiments, the mass fraction of polyethylene terephthalate in the surface layer is 50wt.% to 60wt.%, specifically, the mass fraction of polyethylene terephthalate in the surface layer is 50wt.%, 51wt.%, 52wt.%, 53wt.%, 54wt.%, 55wt.%, 56wt.%, 57wt.%, 58wt.%, 59wt.%, 60wt.%. It can be understood that PET material has good dimensional stability, is not easy to deform or shrink, and is suitable for printing and packaging applications requiring high precision. In addition, PET material has good weather resistance, can be used for a long time in outdoor environments, and is not easy to age or discolor.

[0036] In some embodiments, the mass fraction of polypropylene in the surface layer is 10wt.% to 20wt.%, specifically, the mass fraction of polypropylene in the surface layer is 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%. In other words, after PP with good toughness and impact resistance is blended with PET, the tensile strength of the printed film can be enhanced, and the processing performance can be improved, and the processing difficulty can be reduced. Especially when used outdoors, PP has good water resistance, gas barrier properties and heat resistance, thereby reducing the sensitivity of the PET component to moisture and improving the stability of the PET component in a humid or hot environment, thereby enhancing the performance of the double-sided printed film.

[0037] In some embodiments, the mass fraction of the modified titanium dioxide in the surface layer is 5wt.%~15wt.%, specifically, the mass fraction of the modified titanium dioxide in the surface layer is 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, and further preferably, the mass fraction of the modified titanium dioxide in the surface layer is 5wt.%~10wt.%. By adding an appropriate amount of modified titanium dioxide to the surface layer, while enhancing the performance of the printed film, the transmittance of the printed film is reduced, thereby improving the clarity and printing quality of the printed pattern, and further enhancing the market competitiveness of the product. And the modified titanium dioxide in the surface layer can interact with the core layer, enhance the interfacial adhesion, and thus improve the tensile and puncture resistance of the printed film.

[0038] In some embodiments, the mass fraction of the additive in the surface layer is 5wt.% to 10wt.%, specifically, the mass fraction of the additive in the surface layer can be 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%. By adding appropriate additives to the printed film, the surface smoothness of the printed film is improved, which is beneficial to the printed pattern and the printing quality. In addition, the added additives can also use additives with whitening effects, so as to improve the processing performance while improving the ultra-white performance of the printed film, and facilitate the blending process.

[0039] In some embodiments, the mass fraction of polyethylene terephthalate in the core layer is 50wt.% to 60wt.%, specifically, the mass fraction of polyethylene terephthalate in the surface layer is 50wt.%, 51wt.%, 52wt.%, 53wt.%, 54wt.%, 55wt.%, 56wt.%, 57wt.%, 58wt.%, 59wt.%, 60wt.%. It can be understood that PET material has a wide range of application prospects in the fields of printing and packaging, and has good mechanical properties, chemical stability, thermal stability and environmental protection characteristics, making it an ideal raw material for printing products.

[0040] In some embodiments, the mass fraction of polypropylene in the core layer is 20wt.% to 30wt.%, specifically, the mass fraction of polypropylene in the core layer is 20wt.%, 21wt.%, 22wt.%, 23wt.%, 24wt.%, 25wt.%, 26wt.%, 27wt.%, 28wt.%, 29wt.%, 30wt.%. By adding more PP to the core layer, its mechanical properties and weather resistance as a support layer are enhanced, thereby enhancing the stability of the printed film during use.

[0041] In some embodiments, the mass fraction of the modified titanium dioxide in the core layer is 10wt.% to 20wt.%, specifically, the mass fraction of the modified titanium dioxide in the core layer is 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, and further preferably, the mass fraction of the modified titanium dioxide in the core layer is 15wt.% to 20wt.%. By adding more modified titanium dioxide to the core layer, the ultra-white performance of the core layer is enhanced, the transmittance of the printed film is further reduced, and the printing effect as a raw material for printed products is improved.

[0042] In some embodiments, the mass fraction of modified titanium dioxide in the core layer is greater than the mass fraction of modified titanium dioxide in the surface layer. Since more modified titanium dioxide in the core layer can interact with the surface layers on both sides, the interfacial adhesion is enhanced, the adhesion between the surface layers on both sides and the core layer is increased, and the tensile and puncture resistance of the printed film is further enhanced.

[0043] In some embodiments, the particle size of the modified titanium dioxide is 30nm to 60nm. It is understandable that nano-particle titanium dioxide has a higher refractive index and can effectively scatter and absorb light. This makes the printed film with nano-particle titanium dioxide show a lower transmittance in the visible light range. Furthermore, nano-particle titanium dioxide has a strong absorption capacity for ultraviolet rays and can effectively block the penetration of ultraviolet rays. This not only improves the opacity of the printed film, but also protects the printed film from degradation caused by ultraviolet rays, further extending the service life of the printed film.

[0044] In other words, nano-particle titanium dioxide, as a common filler used in polymers, can improve the tensile strength and toughness of printed films, and nano-particle titanium dioxide has good dispersion in printed films, enhancing the overall uniformity and stability of printed films. Furthermore, nano-particle titanium dioxide can also improve the flatness and glossiness of the printed film surface, which is conducive to printing patterns on the printed film, making the appearance of the printed product more uniform and beautiful, which is very important for application fields that require high surface quality, such as advertising films, decorative films and other applications.

[0045] In some embodiments, the additives include fluorescent whitening agents, stearic acid amide, oleic acid amide, nano calcium carbonate and zinc oxide. It is understood that the use of fluorescent whitening agents on the surface layer can significantly improve the whiteness and brightness of the printed film, and is conducive to enhancing weather resistance and thermal stability, and still maintains a stable whitening effect under high temperature and light conditions, thereby reducing the light transmittance of the printed film, thereby enhancing the stability of the printed product.

[0046] By adding stearic acid amide and oleic acid amide, the smoothness and flatness of the printed film can be improved, and the processing performance can be improved during the processing, the melt viscosity can be reduced, and the dispersion uniformity of the remaining components can be improved. Furthermore, stearic acid amide and oleic acid amide have a certain antistatic effect, which can reduce the accumulation of dust and other impurities on the surface of the printed product, and at the same time improve the waterproof and moisture-proof performance of the printed film, thereby enhancing the use performance of the printed film.

[0047] By adding nano calcium carbonate and zinc oxide, light can be effectively scattered, light penetration can be reduced, the whiteness and glossiness of the printed film can be improved, and thus the opacity of the printed film can be improved. Furthermore, adding nano calcium carbonate and zinc oxide can also improve the toughness, tensile strength and wear resistance of the printed film, and improve the performance of the film.

[0048] In some embodiments, the mass fraction of the fluorescent whitening agent in the auxiliary agent is 10wt.% to 20wt.%, specifically, the mass fraction of the fluorescent whitening agent in the auxiliary agent is 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%. The fluorescent whitening agent has a good whitening effect, which can significantly improve the whiteness and brightness of the printed film, and can achieve an ideal whitening effect even at a low addition amount, further improving the opacity of the printed film.

[0049] In some embodiments, the fluorescent brightener includes one or more of fluorescent brightener OB, fluorescent brightener OB-1 and fluorescent brightener KSN. By selecting a fluorescent brightener with good heat resistance and weather resistance, the service life of the printed film is extended while the performance of the printed film is improved.

[0050] In some embodiments, the mass fraction of stearic acid amide in the auxiliary agent is 10wt.% to 20wt.%, specifically, the mass fraction of stearic acid amide in the auxiliary agent is 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%. By adding stearic acid amide, the smoothness and flatness of the printed film can be improved, and the processing performance can be improved during the processing, the melt viscosity can be reduced, and the dispersion uniformity of the other components can be improved.

[0051] In some embodiments, the mass fraction of oleic acid amide in the additive is 5wt.% to 15wt.%, specifically, the mass fraction of oleic acid amide in the additive is 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%. By adding oleic acid amide, the smoothness and flatness of the printed film can be improved, and the processing performance can be improved during the processing, the melt viscosity can be reduced, and the dispersion uniformity of the other components can be improved.

[0052] In some embodiments, the mass fraction of nano calcium carbonate in the additive is 30wt.% to 45wt.%, specifically, the mass fraction of nano calcium carbonate in the additive is 30wt.%, 32wt.%, 34wt.%, 36wt.%, 38wt.%, 40wt.%, 42wt.%, 44wt.%, 45wt.%. Nano calcium carbonate has a high specific surface area and good dispersibility, can effectively scatter light, reduce light penetration, and thus improve the opacity of the printed film.

[0053] In some embodiments, the mass fraction of zinc oxide in the additive is 15wt.% to 25wt.%. Specifically, the mass fraction of zinc oxide in the additive is 15wt.%, 16wt.%, 17wt.%, 18wt.%, 19wt.%, 20wt.%, 21wt.%, 22wt.%, 23wt.%, 24wt.%, and 25wt.%. Zinc oxide has a high refractive index and good photocatalytic activity, can absorb ultraviolet rays and scatter visible light, and further reduce the light transmittance of the printed film.

[0054] In some embodiments, the first temperature in step S500 is 140° C. to 200° C., specifically, the first temperature is 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., and more preferably, the first temperature is 140° C. to 180° C. By selecting a suitable grafting reaction temperature, the grafting efficiency of the modified titanium dioxide can be further improved.

[0055] In some embodiments, the reaction time of the grafting reaction in step S500 is 40 min to 80 min, specifically, the reaction time is 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, and more preferably, the reaction time is 50 min to 70 min. By selecting an appropriate grafting reaction time, the grafting efficiency of the modified titanium dioxide can be further improved.

[0056] In some embodiments, the thickness of the surface layer is 40 μm to 80 μm, specifically, the thickness of the surface layer is 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm. By selecting a suitable surface layer thickness, it is beneficial to improve the printing pattern effect of the printed film, maintain good mechanical properties and performance, and reduce the possibility of damage.

[0057] In some embodiments, the thickness of the core layer is 200 μm to 400 μm, specifically, the thickness of the core layer is 200 μm, 250 μm, 300 μm, 350 μm, 400 μm. By selecting a suitable thickness of the core layer, the mechanical strength of the support layer is improved, thereby enhancing the tensile and puncture resistance of the printed film.

[0058] According to another aspect of the present application, a method for preparing a double-sided printed film is also provided, comprising the steps of: A100, mixing the modified titanium dioxide and the additive by a high-speed mixer to obtain a first filler; A200, the first filler, polyethylene terephthalate and polypropylene are mixed by a high-speed mixer and then injection molded to obtain a surface layer; A300, modified titanium dioxide, polyethylene terephthalate and polypropylene are mixed by a high-speed mixer and then injection molded to obtain a core layer; A400, the surface layer and the core layer are co-extruded to obtain a double-sided printed film.

[0059] The double-sided printed film obtained by co-extrusion of the surface layer and the core layer has good interface adhesion, thereby enhancing the tensile strength and puncture resistance of the double-sided printed film, and is suitable for maintaining good use stability in various application environments. The preparation method provided in this application is simple in steps and has the potential for large-scale production, increasing production efficiency and thus enhancing market competitiveness.

[0060] Example 1 A double-sided printing film is composed of three layers of composite materials, wherein the middle layer is a core layer and both sides of the core layer are surface layers. The surface layer comprises the following components in weight percentage: 58wt.% of PET, 20wt.% of PP, 14wt.% of modified titanium dioxide, 3.5wt.% of nano calcium carbonate, 2.5wt.% of zinc oxide, 1.5wt.% of stearic acid amide, 1.5wt.% of oleic acid amide, and 1wt.% of fluorescent whitening agent; the core layer comprises the following components in weight percentage: 55wt.% of PET, 28wt.% of PP, and 17wt.% of modified titanium dioxide.

[0061] Example 2 The difference between Example 2 and Example 1 is that the surface layer includes the following components in weight percentage: the mass fraction of PET is 59wt.%, the mass fraction of PP is 20wt.%, the mass fraction of modified titanium dioxide is 13wt.%, the mass fraction of nano-calcium carbonate is 3.5wt.%, the mass fraction of zinc oxide is 2.5wt.%, the mass fraction of stearic acid amide is 1.5wt.%, the mass fraction of oleic acid amide is 1.5wt.%, and the mass fraction of fluorescent whitening agent is 1wt.%.

[0062] Example 3 The difference between Example 3 and Example 1 is that the surface layer includes the following components in weight percentage: the mass fraction of PET is 57wt.%, the mass fraction of PP is 20wt.%, the mass fraction of modified titanium dioxide is 15wt.%, the mass fraction of nano-calcium carbonate is 3.5wt.%, the mass fraction of zinc oxide is 2.5wt.%, the mass fraction of stearic acid amide is 1.5wt.%, the mass fraction of oleic acid amide is 1.5wt.%, and the mass fraction of fluorescent whitening agent is 1wt.%.

[0063] Example 4 The difference between Example 4 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 57wt.%, the mass fraction of PP is 28wt.%, and the mass fraction of modified titanium dioxide is 15wt.%.

[0064] Example 5 The difference between Example 5 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 53wt.%, the mass fraction of PP is 28wt.%, and the mass fraction of modified titanium dioxide is 19wt.%.

[0065] Example 6 The difference between Example 6 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 60wt.%, the mass fraction of PP is 28wt.%, and the mass fraction of modified titanium dioxide is 19wt.%.

[0066] Example 7 The difference between Example 7 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 53wt.%, the mass fraction of PP is 28wt.%, and the mass fraction of modified titanium dioxide is 19wt.%.

[0067] Example 8 The difference between Example 8 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 53wt.%, the mass fraction of PP is 28wt.%, and the mass fraction of modified titanium dioxide is 19wt.%.

[0068] Example 9 The difference between Example 9 and Example 1 is that the surface layer includes the following components in weight percentage: the mass fraction of PET is 68wt.%, the mass fraction of PP is 10wt.%, and the mass fraction of modified titanium dioxide is 14wt.%.

[0069] Example 10 The difference between Example 10 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 48wt.%, the mass fraction of PP is 30wt.%, and the mass fraction of modified titanium dioxide is 14wt.%.

[0070] Embodiment 11 The difference between Example 11 and Example 1 is that the core layer includes the following components in weight percentage: the mass fraction of PET is 58wt.%, the mass fraction of PP is 20wt.%, and the mass fraction of modified titanium dioxide is 14wt.%.

[0071] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the titanium dioxide used is not modified.

[0072] Performance Evaluation The tensile strength of the double-sided printed films in Examples 1 to 11 and Comparative Example 1 was tested according to GB / T 1040.3, the haze was tested according to GB / T 2410, the light transmittance of each group of films was analyzed using an ultraviolet-visible spectrophotometer with a scanning wavelength of 200 nm to 800 nm, the oxygen permeability was tested according to ASTM D1434-23, and the water vapor permeability was tested according to ASTM E96. The test results are shown in Table 1.

[0073] Table 1: Performance test of double-sided printing film

[0074] It is understandable that different modified titanium dioxide contents make the prepared double-sided printed films have different properties. Referring to Example 1, Example 2 and Example 4, when the content of modified titanium dioxide is low in the surface layer or the core layer, the tensile strength of the double-sided printed film is low, the haze is reduced, and the transmittance is increased, indicating that the opacity of the double-sided printed film is poor. Referring to Example 1, Example 3 and Example 5, when the content of modified titanium dioxide is high in the surface layer or the core layer, the filler is prone to uneven dispersion, which reduces the toughness of the printed film and thus reduces the mechanical strength of the printed film. Furthermore, due to the better interlayer adhesion, the barrier properties to oxygen and water vapor are enhanced. The lower oxygen permeability and water vapor permeability in Table 1 also show that the printed film after using modified titanium dioxide has better weather resistance, is suitable for a variety of use environments, and enhances market competitiveness.

[0075] It can be seen from Examples 1, 6, 7 and 8 that when the content of modified titanium dioxide in the core layer is less than that in the surface layer, the modified titanium dioxide in the core layer is difficult to produce good adhesion with the surface layer, thereby reducing the bonding performance between the core layer and the surface layer. Furthermore, as the content of modified titanium dioxide decreases, the opacity of the printed film decreases accordingly.

[0076] Referring to Example 1, Example 9 and Example 10, it can be seen that by adjusting the component ratio between PET and PP in the surface layer, when the proportion of PP reaches 30%, the interfacial force between the two phases may be small, the dispersed phase size is large and the distribution is uneven, thereby reducing the adhesion between the modified titanium dioxide and the PP component, and further reducing the mechanical properties of the printed film. On the one hand, the light-proof performance of the printed film is reduced. On the other hand, due to the decrease in adhesion, the barrier performance of the interlayer to water vapor and oxygen decreases accordingly. In other words, when the proportion of PP is low, since PET dominates the system, the toughness and elongation at break of the printed film may be reduced.

[0077] Furthermore, it can be seen from Examples 1 and 11 that when the ratio of PET to PP components in the core layer and the surface layer is consistent, the printed film prepared in Example 1 has a slight advantage in mechanical strength and opacity over the printed film prepared in Example 11. However, since the price of PP is lower than that of PET, the printed film prepared in Example 1 has the advantage of a lower price, which is beneficial to reducing production costs.

[0078] It can be seen from Example 1 and Comparative Example 1 that since modified titanium dioxide that can react with PET and PP is not introduced into the printed film, the compatibility and adhesion between the components and the layers in Comparative Example 1 are poor, thereby significantly reducing the mechanical strength of the printed film. Furthermore, due to the poor adhesion between the layers, the oxygen permeation rate and the water vapor permeation rate are high, indicating that the printed film in Comparative Example 1 has poor weather resistance and performance.

[0079] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A double-sided printing film, characterized in that: The double-sided printing film is composed of a three-layer composite material, wherein the middle layer is a core layer, and both sides of the core layer are surface layers; The surface layer is prepared from polyethylene terephthalate, polypropylene, modified titanium dioxide and additives; The core layer is made of polyethylene terephthalate, polypropylene and modified titanium dioxide.

2. The double-sided printing film according to claim 1, characterized in that: The modified titanium dioxide is titanium dioxide with polypropylene grafted with maleic anhydride on the surface.

3. The double-sided printing film according to claim 1, characterized in that: The mass fraction of the polyethylene terephthalate in the surface layer is 50wt.%~60wt.%, the mass fraction of the polypropylene is 10wt.%~20wt.%, the mass fraction of the modified titanium dioxide is 5wt.%~15wt.%, and the mass fraction of the auxiliary agent is 5wt.%~10wt.%.

4. The double-sided printing film according to claim 1, characterized in that: The mass fraction of the polyethylene terephthalate in the core layer is 50wt.%~60wt.%, the mass fraction of the polypropylene is 20wt.%~30wt.%, and the mass fraction of the modified titanium dioxide is 10wt.%~20wt.%.

5. The double-sided printing film according to claim 1, characterized in that: The mass fraction of modified titanium dioxide in the core layer is greater than the mass fraction of modified titanium dioxide in the surface layer.

6. The double-sided printing film according to claim 1, characterized in that: The thickness of the surface layer is 40 μm to 80 μm, the thickness of the core layer is 200 μm to 400 μm, the particle size of the modified titanium dioxide is 30 nm to 60 nm, and the auxiliary agents include fluorescent whitening agent, stearic acid amide, oleic acid amide, nano calcium carbonate and zinc oxide.

7. The double-sided printing film according to claim 6, characterized in that: Among the auxiliary agents, the mass fraction of the fluorescent whitening agent is 10wt.%~20wt.%, the mass fraction of the stearic acid amide is 10wt.%~20wt.%, the mass fraction of the oleic acid amide is 5wt.%~15wt.%, the mass fraction of the nano-calcium carbonate is 30wt.%~45wt.%, and the mass fraction of the zinc oxide is 15wt.%~25wt.%.

8. The double-sided printing film according to claim 2, characterized in that: The preparation steps of the modified titanium dioxide are: S100, putting titanium dioxide powder into anhydrous ethanol and performing ultrasonic treatment for 10 min to 30 min to obtain a first solution; S200, placing the first solution into a mixed solution of a silane coupling agent and anhydrous ethanol, stirring and reacting for 1 h to 3 h to obtain a first mixture; S300, centrifugally treating the first mixture, washing and drying the solid matter obtained by the centrifugation to obtain a first powder; S400, providing a mixed solution of xylene and ethanol, and placing the first powder and polypropylene grafted maleic anhydride into the mixed solution to obtain a second mixture; S500, adding dibenzoyl peroxide to the second mixture, raising the temperature to perform a grafting reaction, and obtaining a third mixture; S600, the third mixture is centrifuged, and the solid matter obtained by the centrifugation is washed and dried to obtain modified titanium dioxide.

9. The double-sided printing film according to claim 8, characterized in that: The ratio of the molar number n1 of maleic anhydride groups in the polypropylene grafted maleic anhydride to the molar number n2 of epoxy groups in the first powder is: 1 / 10≤n1:n2≤1 / 2.

10. A method for preparing a double-sided printing film, characterized in that: Includes steps: A100, mixing the modified titanium dioxide and the additive by a high-speed mixer to obtain a first filler; A200, mixing the first filler, polyethylene terephthalate and polypropylene by a high-speed mixer and then performing injection molding to obtain a surface layer; A300, the modified titanium dioxide, polyethylene terephthalate and polypropylene are mixed by a high-speed mixer and then injection molded to obtain a core layer; A400, the surface layer and the core layer are co-extruded to obtain the double-sided printed film.

Citation Information

Patent Citations

  • Semi-transparent polyester film

    CN104809963A

  • Antiblocking agent masterbatch for plastic film and preparation method of antiblocking agent masterbatch

    CN109181242A

  • High-reflectivity polyester film, high-reflectivity photovoltaic module back plate, photovoltaic module, and application of photovoltaic module

    CN111559148A

  • Stress whitening-resistant antibacterial polypropylene composition and preparation method thereof

    CN111825920A

  • High-temperature-resistant toner and preparation method thereof

    CN116656004A